2021
DOI: 10.3390/nu13093281
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Digital Health Intervention Engagement and Dietary Intake: A Systematic Review

Abstract: There has been a proliferation of digital health interventions (DHIs) targeting dietary intake. Despite their potential, the effectiveness of DHIs are thought to be dependent, in part, on user engagement. However, the relationship between engagement and the effectiveness of dietary DHIs is not well understood. The aim of this review is to describe the association between DHI engagement and dietary intake. A systematic search of four electronic databases and grey literature for records published before December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
(135 reference statements)
0
7
0
Order By: Relevance
“…The ordering of the text messages was variable across participants, and due to the observational nature of this study, we cannot determine the extent that ordering may have impacted results; however, the average response rates and trends across message versions and waves provide general insights on how these variations may impact engagement. Finally, we did not assess the impact of engagement on outcomes, as this fell outside the scope of our study; however, other studies in digital health have examined this association [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ordering of the text messages was variable across participants, and due to the observational nature of this study, we cannot determine the extent that ordering may have impacted results; however, the average response rates and trends across message versions and waves provide general insights on how these variations may impact engagement. Finally, we did not assess the impact of engagement on outcomes, as this fell outside the scope of our study; however, other studies in digital health have examined this association [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Examples of user experience outcomes include user satisfaction, acceptability, attention, and usability [ 22 ]. Similarly to previous reviews, engagement could be assessed via any objective or subjective quantitative measure, for example, via embedded data collection systems (ie, DHI analytics) or observation (eg, eye tracking) or as measured using self-reported questionnaires or surveys (eg, user satisfaction questionnaires) [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the impact of strategies on health risk outcomes was mixed, with only 41% (14/34) of overweight-and obesity-related outcomes, 73% (24/33) of physical activity-related outcomes, and 47% (7/15) of nutrition-related outcomes found to be positive and in the hypothesized direction. Although previous reviews have demonstrated the effectiveness of DHIs in improving health outcomes [25][26][27], this is the first review to synthesize the effects of strategies to improve engagement with DHIs on health outcomes, and so comparisons cannot be drawn.…”
Section: Comparisons With Other Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the short-term (3 months), higher-frequency feedback produced larger improvements in overall diet quality as well as in markers of adiposity but only differences in body weight and BMI remained significant at 6 months [ 142 ]. Although not focused specifically on personalised nutrition, a recent systematic review that synthesized the evidence for associations between DHI engagement and dietary intake reported that some evidence supported an association with usage of the digital support but that this evidence was inconsistent [ 143 ].…”
Section: Translation Of Nutrigenomic Research For Personalised and Pr...mentioning
confidence: 99%